Effects of Alcohol Excise Tax on Alcohol Consumption in Thailand - Raksong, Saranya; Meunthaisong, Kesinee; Buawaroon Sriwichai, Buawaroon (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
Thailand is the one of the highest alcohol consuming country. This leads to the country’s negative social and economic effects. Therefore, the Thai government pays attention to reducing the negative effects by collecting alcohol excise taxes. As higher alcohol excise taxes lead to higher prices of alcohol drink, alcohol consumption is likely to decrease. The purpose of this paper is to investigate the effects of alcohol excise taxes on the levels of alcohol consumption in Thailand. The research is conducted by using secondary quarterly data from 1997Q1 to 2013Q4. There are four alcohol beverages included in this paper: white spirit, blend spirit, special blend spirit, and special spirit. Co-integration method is applied to investigate long run effects of alcohol taxes on the levels of alcohol consumption in Thailand while the short run effects of alcohol taxes on the levels of alcohol consumption in Thailand is tested by using Vector Error Correction Model. The results indicate that alcohol excise taxes have negative effects on the levels of consumption of blend spirit, special blend spirit, and special spirit in Thailand. However, the alcohol excise tax has no significant effect on white spirit, both in the short run and long run